Pengaruh Brand Ambassador dan Perilaku Konsumtif terhadap Keputusan Pembelian - Wulan Rivanda Early; Dede R. Oktini; Rezi Muhamad Taufik Permana (Bandung Conference Series: Business and Management, 2024)
Abstract. The phenomenon of idolizing South Korean boy bands and girl groups, especially focusing on the influence of Brand Ambassadors and Army consumptive behavior on purchasing decisions on Tokopedia e-commerce. South Korea, with its global K-pop culture (hallyu or Korean wave), offers entertainment products that are in high demand, especially Korean pop music or K-pop. However, this phenomenon brings not only positive, but also negative impacts, especially in the form of excessive consumptive behavior. This study aims to understand the role of Brand Ambassadors and Army consumptive behavior on Tokopedia, as well as analyze the impact on Army purchasing decisions. The study covers the influence of BTS's celebrity endorsers on Army purchasing decisions, with factors such as willingness to collect, ease of internet access, free shipping, and discount vouchers. The research method used is a survey with quantitative data collection using an online questionnaire. This study used statistical analysis, especially regression, with SPSS program tool version 25. Validity and reliability tests are carried out to ensure the quality of research instruments. Classical assumptions such as normality, multicollinearity, and heteroscedasticity are tested to validate the data. The results of the analysis show that BTS's Brand Ambassadors have a significant influence on ARMY's purchase decisions. Abstrak. Fenomena mengidolakan boyband dan girlband asal Korea Selatan, terutama fokus pada pengaruh Brand Ambassador dan perilaku konsumtif ARMY terhadap keputusan pembelian di e-commerce Tokopedia. Korea Selatan, dengan budaya K-pop yang mencapai tingkat global hallyu atau Korean wave, menawarkan produk hiburan yang sangat diminati, khususnya musik pop Korea atau K-pop. Namun, fenomena ini tidak hanya membawa dampak positif, tetapi juga negatif, terutama dalam bentuk perilaku konsumtif yang berlebihan. Penelitian ini bertujuan untuk memahami peran Brand Ambassador dan perilaku konsumtif ARMY pada Tokopedia, serta menganalisis dampaknya terhadap keputusan pembelian ARMY. Studi ini mencakup pengaruh Brand Ambassador BTS terhadap keputusan pembelian ARMY, dengan faktor-faktor seperti keinginan mengoleksi, kemudahan akses internet, pengiriman gratis, dan voucher diskon. Metode penelitian yang digunakan adalah survei dengan pengumpulan data kuantitatif menggunakan kuesioner melalui gform . Penelitian ini menggunakan analisis statistik, khususnya regresi, dengan alat bantu program SPSS versi 25. Uji validitas dan reliabilitas dilakukan untuk memastikan kualitas instrumen penelitian. Asumsi klasik seperti normalitas, multikolinearitas, dan heteroskedastisitas diuji untuk memvalidasi data. Hasil analisis menunjukkan bahwa Brand Ambassador BTS memiliki pengaruh yang signifikan terhadap keputusan pembelian ARMY.